Analisis Dampak Kebijakan Non-Tarif Measures Terhadap Kinerja Ekspor Udang Beku Indonesia di Pasar Tujuan Utama (Jurnal Agribisnis Indonesia, 2023)
The shrimp commodity significantly contributes to the total export value of the fisheries sub-sector in Indonesia. In 2021, Indonesia will become the fourth largest exporter of frozen shrimp on the world market. However, the value of Indonesia's frozen shrimp exports continues to fluctuate every year. Indonesia's frozen shrimp exports also face various challenges from non-tariff measures (NTM) policies, incredibly sanitary and phytosanitary (SPS) and technical barriers to trade (TBT) imposed by importing countries. This study aims to analyze the performance of Indonesia's frozen shrimp trade in destination markets and the impact of NTM policies and other factors on Indonesian shrimp exports in destination markets. This research uses panel data model regression. The results showed there was still rejection of fishery products including frozen shrimp from Indonesia in importing countries due to excess chemical content. But the number of rejections is less than one percent compared to the total received. This is in line with the panel data regression results for the SPS variable which is not significant and the TBT variable which has a significant and positive effect.  The non-significant results indicate that exporters in Indonesia can adjust the policies imposed by the importing country relating to product certification criteria, sampling procedures, packaging requirements, distribution requirements, and labeling requirements. For this reason, the Indonesian government needs to improve regarding rejection is the need for accurate and thorough sample testing of Indonesian frozen shrimp before export, as well as increasing assistance regarding threshold limits for chemical use for shrimp cultivators at the upstream level.